Immunity and Extracellular Matrix Characteristics of Breast Cancer Subtypes Based on Identification by T Helper Cells Profiling - Zhou, Yan; Tian, Qi; Gao, Huan; Zhu, Lizhe; Zhang, Ying; Zhang, Chenchen; Yang, Jiao; Wang, Bo (Frontiers in Immunology, 2022)
Background The therapeutic effect of immune checkpoint inhibitors on tumors is not only related to CD8+ effector T cells but also sufficiently related to CD4+ helper T (TH) cells. The immune characteristics of breast cancer, including gene characteristics and tumor-infiltrating lymphocytes, have become significant biomarkers for predicting prognosis and immunotherapy response in recent years. Methods Breast cancer samples from The Cancer Genome Atlas (TCGA) database and triple-negative breast cancer (TNBC) samples from GSE31519 in the Gene Expression Omnibus (GEO) database were extracted and clustered based on gene sets representing TH cell signatures. CIBERSORT simulations of immune cell components in the tumor microenvironment and gene set enrichment analyses (GSEAs) were performed in the different clusters to verify the classification of the subtypes. The acquisition of differentially expressed genes (DEGs) in the different clusters was further used for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. The clinical information from different clusters was used for survival analysis. Finally, the surgical tissues of TNBC samples were stained by immunofluorescence staining and Masson’s trichrome staining to explore the correlation of TH cell subtypes with extracellular matrix (ECM). Results The breast cancer samples from the datasets in TCGA database and GEO database were classified into TH-activated and TH-silenced clusters, which was verified by the immune cell components and enriched immune-related pathways. The DEGs of TH-activated and TH-silenced clusters were obtained. In addition to TH cells and other immune-related pathways, ECM-related pathways were found to be enriched by DEGs. Furthermore, the survival data of TCGA samples and GSE31519 samples showed that the 10-year overall survival (p-value < 0.001) and 10-year event-free survival (p-value = 0.162) of the TH-activated cluster were better, respectively. Fluorescent labeling of TH cell subtypes and staining of the collagen area of surgical specimens further illustrated the relationship between TH cell subtypes and ECM in breast cancer, among which high TH1 infiltration was related to low collagen content (p-value < 0.001), while high TH2 and Treg infiltration contained more abundant collagen (p-value < 0.05) in TNBC. With regard to the relationship of TH cell subtypes, TH2 was positively correlated with Treg (p-value < 0.05), while TH1 was negatively correlated with both of them. Conclusions The immune and ECM characteristics of breast cancer subtypes based on TH cell characteristics were revealed, and the relationship between different TH cell subsets and ECM and prognosis was explored in this study. The crosstalk between ECM and TH cell subtypes formed a balanced TME influencing the prognosis and treatment response in breast cancer, which suggests that the correlation between TH cells and ECM needs to be further emphasized in future breast cancer studies.